Understanding Mechanism of Photocatalytic Microbial Decontamination of Environmental Wastewater - Regmi, Chhabilal; Joshi, Bhupendra; Ray, Schindra K.; Gyawali, Gobinda; Pandey, Ramesh P. (Frontiers in Chemistry, 2018)
Several photocatalytic nanoparticles are synthesized and studied for potential application for the degradation of organic and biological wastes. Although these materials degrade organic compounds by advance oxidation process, the exact mechanisms of microbial decontamination remains partially known. Understanding the real mechanisms of these materials for microbial cell death and growth inhibition helps to fabricate more efficient semiconductor photocatalyst for large-scale decontamination of environmental wastewater or industries and hospitals/biomedical labs generating highly pathogenic bacteria and toxic molecules containing liquid waste by designing a reactor. Recent studies on microbial decontamination by photocatalytic nanoparticles and their possible mechanisms of action is highlighted with examples in this mini review.